An orientation to be a good millennial Muslims: state and the politics of naming in islamizing Java - Askuri Askuri; Joel C Kuipers (IAIN Salatiga, 2019)
Traditionally, Javanese names pretend to be social classifications (priyayi class, santri class, abangan class, lower class, noble class, etc.) and as a marker of time or condition when they were born. In the last 30 years, however, the naming tradition has been increasingly abandoned by a new generation of parents in Java by taking on new names that have never existed in Javanese treasury of names: its linguistic variation is wider and has a future-oriented meaning for their children. Does the shift of meaning in naming have a close connection with Islamization in Java, since this change involves a large number of Arabic names which are one of the Islamic registers in this country? With a naming approach that processed almost one million names from Bantul, this research proves clearly about the indirect role of the state in the growth of Islamic orientation of new generation of parents in Java. They want to connect the future of their children with Islam. Millennial Muslims generation has been indirectly shaped by this new generation of parents through naming, in which new world that parents want to build for their children is linked to Islam through the Arabic names that have the orientation to become a good Muslim in the millennial era. Secara tradisional, nama-nama Jawa bisa menjadi penanda klasifikasi sosial (kelas priyayi, kelas santri, kelas abangan, kelas bawah, kelas bangsawan, dan lain-lain), sekaligus sebagai penanda waktu atau kondisi ketika mereka dilahirkan. Namun, dalam 30 tahun terakhir, tradisi penamaan tersebut semakin ditinggalkan oleh generasi baru orang tua di Jawa dengan menggunakan nama-nama baru yang tidak pernah ada dalam perbendaharaan nama Jawa: variasi linguistiknya lebih luas dan memiliki makna berorientasi masa depan. Apakah pergeseran makna dalam penamaan memiliki hubungan yang dekat dengan Islamisasi di Jawa, mengingat perubahan ini melibatkan sejumlah besar nama Arab yang merupakan salah satu register keislaman di negeri ini? Dengan pendekatan penamaan yang memproses hampir sejuta nama penduduk di Kabupaten Bantul, penelitian ini membuktikan dengan jelas tentang peran negara secara tidak langsung dalam pertumbuhan orientasi keislaman generasi baru orangtua di Jawa. Mereka ingin menghubungkan masa depan anak-anak mereka dengan Islam. Generasi Muslim milenial telah secara tidak langsung dibentuk oleh generasi baru orang tua ini melalui penamaan, di mana dunia baru yang mereka inginkan untuk anak-anak mereka terkait dengan Islam melalui nama-nama Arab yang memiliki orientasi untuk menjadi Muslim yang baik di era milenial.